2018
DOI: 10.3389/fmicb.2018.01723
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Lowers Streptococcus suis serotype 2 Pathogenicity in Mice by Inhibiting the Hemolytic Activity of Suilysin

Abstract: Streptococcus suis serotype 2 is a serious zoonotic pathogen and has attracted worldwide attention since the first human case was reported in Denmark in 1968. Some virulence factors have been reported to be involved in the pathogenesis of the infection caused by Streptococcus suis serotype 2, and then novel strategies to identify some anti-virulence compounds which can effectively inhibit the pathogenic bacterial infection have recently been reported. Suilysin is an essential virulence factor for Streptococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…The results showed that apigenin significantly inhibited the production of TNF-α, IL-1β, and IL-6 in the supernatant of J774 cells infected with SS2 in a dose-dependent manner. In addition, apigenin in combination with the first-line drug ampicillin decreased the levels of blood biochemical markers (ALT, AST, CK) and the bacterial load in the tissues of the mice infected with SS2 strain SC19, which contributed to the higher survival rate of infected mice when compared with the infected mice treated with the single anti-hemolysin compound fisetin in our study [ 11 ]. More importantly, the values of transaminases in infected mice were indicative of improvements in liver levels, which also suggested that apigenin may have an important hepato-reparative or hepato-protective effect.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The results showed that apigenin significantly inhibited the production of TNF-α, IL-1β, and IL-6 in the supernatant of J774 cells infected with SS2 in a dose-dependent manner. In addition, apigenin in combination with the first-line drug ampicillin decreased the levels of blood biochemical markers (ALT, AST, CK) and the bacterial load in the tissues of the mice infected with SS2 strain SC19, which contributed to the higher survival rate of infected mice when compared with the infected mice treated with the single anti-hemolysin compound fisetin in our study [ 11 ]. More importantly, the values of transaminases in infected mice were indicative of improvements in liver levels, which also suggested that apigenin may have an important hepato-reparative or hepato-protective effect.…”
Section: Discussionmentioning
confidence: 86%
“…SLY was reported to lyse red blood cells to release hemoglobin along with S. suis cell wall components to increase the levels of proinflammatory mediators in vivo [ 9 ]. In some previous studies, the virulence of SS2 was reduced by flavonoids, including apigenin and fisetin, which can weaken the pathogenicity of SS2 by inhibiting the hemolytic activity of SLY [ 10 , 11 , 12 ]. S. suis with high levels of SLY is more likely to cause mortality in infected models when compared with nonvirulent strains, indicating that the pathogenicity of S. suis can be enhanced by increasing the production of SLY [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the experiment, all the mice were euthanized by CO 2 inhalation. Cytokines were quantified using a sensitive platform based on electrochemical luminescence (Quickplex, Meso-Scale Discovery ® , Kenilworth, MD, USA) [ 42 ]. To assess the pathological changes caused by bacteria, the left lobe of each mouse lung was fixed in 4% paraformaldehyde for pathological examination.…”
Section: Methodsmentioning
confidence: 99%
“…inoculated with PCN033 and mutant ΔvgrG1Δ0248ΔvgrG2Δ1588 at approximate 1 × 10 6 CFU. Mice were monitored for 336 hours (14 days) and survival rates were recorded as described in a previous study [92]. Five-week-old female BALB/c mice used for bacteria colonization were randomly divided into groups of five and were intravenously (i.v.)…”
Section: Animal Experimentsmentioning
confidence: 99%